Human Umbilical Cord MSC Delivered-Soluble TRAIL Inhibits the Proliferation and Promotes Apoptosis of B-ALL Cell In Vitro and In Vivo - Fangshan Chen; Xianmei Zhong; Qian Dai; Kuo Li; Wei Zhang; Jie Wang; Yueshui Zhao; Jing Shen; Zhangang Xiao; Hongyun Xing; Jing Li (MDPI AG, 2022)
The TNF-related apoptosis-inducing ligand (TRAIL) could induce apoptosis of leukemic cells, while showed no cytotoxic effect on normal cells. One of the limitations for application of recombinant TRAIL (rhTRAIL) in leukemia treatment is that the serum half-life of this protein is short. Gene delivery is a good strategy to prolong the half-life of TRAIL. In this study, we genetically engineered umbilical cord-MSCs to continuously express and secrete soluble TRAIL (MSC-sTRAIL), to investigate the effects of MSC-sTRAIL on B-cell acute lymphocytic leukemia (B-ALL) cells. In vitro, MSC-sTRAIL significantly inhibited the proliferation of B-ALL cells by suppressing PI3K/AKT and MEK/ERK signaling pathways, and induced apoptosis of B-ALL cells via the caspase cascade-mediated pathway and mitochondrial-mediated pathway. In vivo, MSC-sTRAIL dramatically inhibited B-ALL cell growth. Meanwhile, B-ALL-induced splenic and renal injuries were significantly alleviated after MSC-sTRAIL treatment. Moreover, the serum levels of MSC-secreted sTRAIL were still high in MSC-sTRAIL treated mice, indicating an extended half-life of sTRAIL. Our study suggests that MSC delivered-TRAIL secretion is a potential therapeutic strategy for B-ALL treatment.